Justifiability as grounds for the review of labour arbitration proceedings - Young, Kirsty Leigh (Rhodes University, Faculty of Law, Law, 2004)
This thesis focuses on the review of labour arbitration awards given under the auspices of the following bodies: the Commission for Conciliation, Mediation and Arbitration ("CCMA"), bargaining councils, statutory councils, accredited private agencies and private arbitration tribunals. The general grounds of review applicable to the arbitration awards of each body are set out. Against this background, the case of Carephone (Pty) Ltd v Marcus NO & Others (1998) 19 ILJ 1425 (LAC) is analysed and the principles pertaining to the justifiability test are clarified. The judicial rationale for the application of the test to CCMA arbitration proceedings and criticisms of the test are then examined. Currently the justifiability test applies in the review of CCMA proceedings only, so the judicial reasoning for the rejection of justifiability as a ground for private arbitration review is examined. Three approaches are suggested for the application of the justifiability test in private arbitration review. First it is proposed that the Arbitration Act could be interpreted to include the justifiability test under the statutory review grounds. Failing the acceptance of this approach, the second submission is that arbitration agreements could be interpreted to include an implied term that the arbitrator is under a duty to give justifiable awards. A third suggestion is that the law should be developed by attaching an ex lege term to all arbitration agreements requiring arbitrators to give justifiable awards. In the final chapter, the requirement of justifiability in awards given under the auspices of collective bargaining agents and accredited private agencies highlights the incongruity in applying the justifiability test in CCMA arbitration review and in rejecting this test in private arbitration review.
Keywords: South Africa. Commission for Conciliation, Mediation and Arbitration; Mediation and conciliation, Industrial -- South Africa; Arbitration, Industrial -- South Africa; Arbitration, Industrial -- Law and legislation -- South Africa